‘God Will Redeem My Soul from Sheol’: The Psalms of the Sons of Korah - Mitchell, David C. (Journal for the study of the Old Testament, 2006)
After defining the Korah collection, this study shows that biblical tradition about the Korahites is marked by the theme of redemption from Sheol. This theme is discussed, particularly in regard to the resurrection of the dead. Then an examination of the Korah Psalms shows that the theme appears there also. Moreover, some of these psalms seem to feature the related idea of the righteous being caught up in the air when the earth opens. These ideas occur in later literature with proof-texts from the Korah Psalms, which would appear to be their source. Correspondences are drawn between these traits of the Korah Psalms and the author’s proposed eschatological programme in the Psalter.